ANALISIS TINGKAT KEBUTURAN ANGKUTAN TAKSI KOTA BANDUNG DENGAN TEKNIK STATED PREFERENCE - KURNIATI, TITI
Good public transport service depends on sosial and economic conditions of the society. Taxi, as part of public transport facility has its own characteristics and market segments which are different from other means of public transport. For this reason, a study on the demand rate of taxi should be conducted. This research is focusing in finding characteristics and determining taxi\'s demand rate in the city of Bandung, which in the future can be used to estimate the number of taxi\'s fleet which are needed in the city of Bandung. \"Person-Category Trip Generation Model\" is used to analyzed taxi\'s demand rate, and \"Multiple Classification Analysis (MCA)\" is used in computation process. The trip rate models were developed, then were tested by statistical test to obtain the best model. The research is also trying to find a figure of the demand on taxi service based on several hypothetical conditions. This, is conducted by Stated Preference design experiment which is analysed by multi-regression approach. The resulted model of taxi choice mode model is also tested by statistical test and the resulted parameter are checked by reasonability criteria. Individual sensitivity respond in choosing taxi mode to the attribute changes is also tested by using elasticity analysis model. The best trip rate model resulted from the statistical test is the model using 12 categories trip rate, which range is 1.033-3.800 trip/week/household, and the number of trip per day is identified by 3 (three) scenarios users proportion, since from this research the actual data of user proportion is not available. On the analysis of stated preference data, the resulted utility function model is fulfilled the statistical test and reasonability criteria parameter requirement. The resulted value of RZ is 0.244 which is considered to be quite small. This, might be caused by choosing inaccurate probability value to transform the utility value. The elasticity of probability of choosing taxi is more sensitive to the change of cost than the change of travel time, the change of income,and the change of service.